Factors predicting staging and treatment initiation for patients with chronic hepatitis C infection: insurance a key predictor. (5th February 2021) - Lin, Janet; Mauntel-Medici, Cammeo; Maheswaran, Anjana Bairavi; Baghikar, Sara; Pugach, Oksana; Stein, Ellen M; Martin, Michelle T; Nguyen, Hai
Abstract: Background: Chronic hepatitis C (HCV) infection affects over 2.4 million Americans and accounts for 18 000 deaths per year. Treatment initiation in this population continues to be low even after introduction of highly effective and shorter duration direct-acting antivirals. This study assesses factors that influence key milestones in the HCV care continuum. Methods: Retrospective time-to-event analyses were performed to assess factors influencing liver fibrosis staging and treatment initiation among individuals confirmed with chronic HCV infection at University of Illinois Hospital and Health Sciences System between 1 August 2015 and 24 October 2016 and followed through 28 January 2018. Cox regression models were utilized for multivariable analyses. Results: Individuals tested at the liver clinic (hazard ratio [HR] = 2.03; 95% confidence interval [CI]: 1.19–3.46) and at the federally qualified health center (HR = 3.51; 95% CI: 2.19–5.64) had higher instantaneous probability of being staged compared with individuals tested at the emergency department (ED) or inpatient setting. And probability of treatment initiation increased with advancing liver fibrosis especially for Medicaid beneficiaries (HR = 1.64; 95% CI: 1.35–1.99). Conclusions: The study demonstrates a need for improving access for patients with early stages of the disease in order to reduce HCV-related morbidity and mortality, especially those tested at nontraditional care locations such as the ED or the inpatient setting.